Design of aperture‐coupled microstrip patch antenna array fed by SIW for 60 GHz band. Issue 3 (1st February 2016) - Mikulasek, Tomas; Lacik, Jaroslav; Puskely, Jan; Raida, Zbynek
Abstract : This study deals with a design procedure and achieved parameters of a microstrip patch antenna array fed by a substrate integrated waveguide (SIW) operating at V‐band. The antenna array consists of 6 × 8 microstrip patch antennas which are aperture coupled with an SIW‐based feeding network. The antenna design is performed in a full‐wave electromagnetic solver (ANSYS HFSS) for the operation frequency 60 GHz. The design procedure of the proposed antenna array comprises the analysis of an isolated radiating element, the synthesis of a linear array, and the development of an SIW‐based power divider. At the operation frequency 60 GHz, a fabricated prototype has an impedance bandwidth of 1.8% for a reflection coefficient lower than −10 dB, a gain of 21.6 dBi, and a low sidelobe level below −23 dB in the E‐plane and H‐plane.